United Nations of Rendang: Meme dalam Perspektif Strukturalisme Lévi-Strauss - Herry Nur Hidayat (Jurnal Lingua Idea, 2019)
This article analized meme United Nations of Rendang through Levi-Struss structuralism perspective. In this case, social an culture seen as a structure which shows human unconsiuous to structuring a phenomenon. Sign interrelation in United Nations of Rendang as a structure automatically relate to the other meme which is another structure. Those sign convey to the surface structure and reveal the deep structure of this phenomenon. As a result, meme United Nations of Rendang shows rejection on Masterchef jury for the criticism on rendang as surface structure. This surface structure lead to awareness of same region country, awareness of western culinary domination, and a rejection for western culinary domination as deep structure.